The Potential Of Women As Peacekeepers Of Religious Moderation (Case Study Of The Wahid Foundation Peace Village Program In Sidomulyo Village, Batu City) - Zeid B. Smeer; Inayatur Rosyidah; Mubasyiroh Mubasyiroh (Green Publisher Indonesia, 2024)
Based on the research that has been conducted, the Wahid Foundation's peace village programme in exploring the role of women as peacekeepers of religious moderation in Desa Dam Desa Sidomulyo Kota Batu targets three important aspects, namely strengthening women's social inclusion through economic independence, social mechanisms of peace and women's empowerment. These three aspects are the basic foundation for strengthening the role of women as peacekeepers of religious moderation in the grassroots community as the motto of the Wahid Foundation's peace village,